Identifying the Role of Media Technology Advances in Economics - Karamouzian, Morteza (2021)
The purpose of this article is to identify the role of media technology development in the economy. In this study, 30 experts in the field of media were used as a sample. The research method is qualitative. Since in this research, there was a need to address the depth of the subject and a deep and comprehensive understanding of media experts, for this reason, the interview method was used. In order for the interviews to have a specific structure, semi-structured interviews have been used. Data were also analyzed through content analysis using maxqda software. In this study, 23 effective factors that determine the positive and negative role of media technologies in the economy were identified, including: information production and increasing economic knowledge, more employment, consumer welfare, reducing economic inequality, reducing political risk, increasing Economic security and efficiency, more control and supervision of people over economic activities, expansion of corporate markets, creation of free online market, innovations and innovations resulting from new technologies increase revenues, increase competition between organizations increase the quality of economic activities, improve and Improving the standards of economic development, public participation in economic activities, expressing people's satisfaction or dissatisfaction with economic activities, spending time on social networks.